Ultrasound shear modulus and thickness of lateral abdominal muscles in different contractile states in relation to self-reported hip/groin problems in youth soccer players - Linek, P.; Booysen, N.; Stokes, M. (Journal of Human Kinetics, 2022)
To date, no studies have assessed lateral abdominal muscles` (LAM) elasticity and thickness in relation to hip and groin symptoms in any population. The objectives were to a) assess the relationship between LAM ultrasound measurements (elasticity and thickness) and self-reported subscales of the Copenhagen Hip and Groin Outcome Score (HAGOS) and b) compare LAM elasticity and thickness between asymptomatic and symptomatic sides. Shear modulus and thickness of the oblique external (OE), internal (OI) and transversus abdominis (TrA) muscles in 25 young soccer players were assessed at rest and during isometric contraction using ultrasound shear wave elastography. HAGOS subscales were used to assess self-reported hip/groin problems. There was a significant (p < 0.05) moderate correlation between allometric-scaled OI resting thickness (mean of right and left) and the Activities of Daily Living (r = 0.40), Sport (r = 0.57) and Quality of Life (QOL) (r = 0.41) HAGOS subscales. Also, a moderate significant correlation was found between allometric-scaled TrA resting thickness and the QOL subscale (r = 0.47). Moderate correlations were found between resting OI shear modulus and the QOL (r = 0.44), between right TrA shear modulus during contraction and Symptoms (r = 0.57), and between the left TrA shear modulus during contraction and Physical Activity (r = 0.41) subscales. No differences were found between the symptomatic and asymptomatic side in thickness and elasticity measurements among soccer players with unilateral symptoms (p > 0.05). The relationships found between LAM and hip/groin problems in youth male soccer players indicate that muscles are thinner and more elastic (less stiff) in more symptomatic athletes.